KARAKTERISTIK ASPAL SEBAGAI BAHAN PENGIKAT YANG DITAMBAHKAN PLASTIK POLYVINYL CHLORIDE ( PVC) - Mashuri, Mashuri (MEKTEK, 2009)
The objective of this research is to know characteristics of bitumen binder mixtures plastic of Polyvinyl Chloride (PVC) powder. This research was done in Highway and transportation laboratory of Civil Department, Tadulako University. Percentage of Polyvinyl Chloride powder content based on weight of bitumen. The percentage of PVC powder in bitumen are 2%, 4%, 6% and 8% respectively and comparison with properties of bitumen without additive material. The properties of bitumen include the following: the penetration value of bitumen, the Ductility value, the softening point value, density of bitumen value, loss on heating of bitumen, flash and fire point of bitumen values.The result of this research indicates that the Polyvinyl Choloride powder in bitumen between 2% to 8% still enough for spesification except on ductility properties of bitumen values. This implies that, increment the Polyvinyl Chloride in bitumen potential influence on asphalt pavement include stiffness and brittle of mixtures